Detection of synovial inflammation in rheumatic diseases using superb microvascular imaging: Comparison with conventional power Doppler imaging. Issue 2 (4th March 2018) - Yokota, Kazuhiro; Tsuzuki Wada, Takuma; Akiyama, Yuji; Mimura, Toshihide
Abstract: Aim: Superb microvascular imaging (SMI), a novel ultrasonography, is based on the sensitivity of Doppler technology. This study evaluated power Doppler (PD) ultrasound signals in patients with rheumatic disease using SMI and conventional PD imaging (cPDI) and compared the correlations of these signals to clinical assessments. Methods: Thirty-nine patients with rheumatic disease (27 rheumatoid arthritis [RA] and 12 non-RA) were enrolled. We investigated SMI and cPDI signals in 26 joints using an Aplio 300. Individual scores were summed to calculate total SMI and cPDI scores. Results: Total SMI scores were significantly higher than total cPDI scores in patients with RA, but not in those with the non-RA disease. Total SMI score was associated with serum levels of C-reactive protein (CRP) and matrix metalloproteinase-3; disease activity score 28-CRP and health assessment questionnaire disability index scores, and SMI were more sensitive to detect active synovitis than cPDI in RA patients. Among the joint regions, the wrists and metacarpophalangeal joints were more sensitive to the detection of synovial inflammation using SMI in patients with RA. Conclusion: SMI was more sensitive in detecting synovial inflammation than cPDI in patients with RA. SMI could be a potentially useful imaging modality for accurately diagnosing and monitoring the disease activity of RA.